Precolonial iron production around Durban and in southern Natal - Whitelaw, G. (Southern African Humanities, 2021)
A terminal Iron Age furnace threatened by suburban development in Cato Manor, Durban, was excavated in 1989. The furnace is of a type previously unknown in Natal and may represent a second Late Iron Age smelting tradition in this region. Speculation concerning the practitioners of this tradition and discussion of the relationship between this furnace and other smelting sites in the Durban area is provided. The discussion is extended to include the distribution of smelting sites in southern Natal, and suggestions concerning where concentrations of smelting sites are likely to be found south of the Mngeni River. To cite this article: Whitelaw, G. 1991. Precolonial iron production around Durban and in southern Natal. Natal Museum Journal of Humanities 3: 29-39.